Psychological Safety and Team Performance: Mapping Key Insights and Emerging Trends - Katarina Božić (Anali Ekonomskog fakulteta u Subotici, 2026)
Purpose: Psychological safety is a central concept in team research, widely recognized as a key driver of team performance. However, the rapidly growing body of research remains conceptually diverse and scattered across multiple disciplinary areas, making it difficult to consolidate dominant themes and new directions. This study maps and synthesizes recent research to identify the field’s intellectual foundations, dominant themes, and emerging research fronts shaping current and future work.Мethodology: This study conducts a bibliometric mapping of literature on psychological safety and team performance from 2018 to 2025, analyzing 278 publications retrieved from the Web of Science Core Collection. VOSviewer and Bibliometrix were used to apply performance analysis and science mapping techniques, including keyword co-occurrence, reference co-citation, and bibliographic coupling.Findings: The results reveal a highly interconnected research landscape in which psychological safety acts as a central hub linking multiple performance-related mechanisms. Dominant themes include leadership, communication and coordination, conflict and diversity, and trust, with recent research highlighting measurement refinement, contextual factors, and practical applications in understanding team performance.Originality: This study systematically maps and synthesizes recent research on psychological safety and team performance, clarifying a fragmented field by identifying its intellectual foundations, key themes, emerging directions, and context-dependent mechanisms with implications for future research and practice.Practical implications: The findings offer decision-makers and team leaders actionable insights to enhance psychological safety, optimize team performance, and tailor management practices to complex, dynamic work environments.Limitations: Future research should expand database coverage and strengthen theoretical integration by exploring multilevel mechanisms, longitudinal designs, and contextual moderators influencing the psychological safety–performance relationship.